Zimbabwe : A Quest for a Nominal Anchor - Kovanen, Arto. (Washington, D.C. : International Monetary Fund, 2004)
This study examines the appropriateness of alternative intermediate monetary policy targets for Zimbabwe in light of the stability of the demand for money and the information content of financial variables for predicting price level movements. Results of the study indicate that a well-defined long-run demand relation exists for currency in circulation, but not for other monetary aggregates. Currency in circulation has strong information content for predicting future price level movements. The information content of other financial variables, such as the exchange rate and interest rates, is weaker. Statistical relationships break down of the outset of high inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet